The Efficacy of Augmented Reality (AR) Gamification in Enhancing Motivation and Academic Performance among Primary School Students in Malaysia when Learning about the Topic of Energy - Sathiya Bharathi A/P Murti; Abdelrahman Ibrahim Suleiman Islaieh; Ummu Salmah Binti Mohamad Hussin; Rossidi Bin Usop; Ahmad Fuad Mohamad Amin; Musa Mohamad (Lectito Publications, 2026)
Indexed by WOS/SCOPUS/ERA